Fodder Beet – A Nutritive and High Yielding Fodder Crop Suitable for Salt Affected Soils of Arid Regions - Tanwar, S PS; Singh, Akath; Deb, S M; Khandelwal, Vikas; Jodha, B S (Annals of Arid Zone, 2016)
An experiment was carried out to study the suitability and yield potential of fodder beet (Beta vulgaris L.) in Western Rajasthan for the first time. under saline irrigation (EC 4 dS m-1), a very high productivity was achieved i.e. fresh fodder yield of 61 and 72.1 t ha-1 harvested at 120 and 150 days after sowing, respectively. Proximate analysis was also carried out and it was found to be an energy rich nutritive fodder. Compared to wheat crop, salt build up was less under fodder beet cultivation (1.11 dS m-1). Therefore, considering huge potential of this crop for producing excellent quality fodder as well as phyto-amelioration of salt affected soils even under saline irrigation this crop should be promoted in arid regions where livestock based farming system is a norm. Key words: Fodder beet, productivity, phyto-amelioration, saline irrigation.